Design of LNA at 5.8GHz with Cascode and Cascaded Techniques Using T-Matching Network for Wireless Applications - Ibrahim, Abu Bakar; Othman, Abdul Rani; Husain, Mohd Nor; Johal, Mohammad Syahrir (2012)
This paper presents the design of low noise amplifier with cascode and cascaded techniques using T-matching network applicable for IEEE 802.16 standards. The amplifier use FHX76LP Low Noise SuperHEMT FET. The design simulation process is using Advance Design System (ADS) software. The cascode and cascaded low noise amplifier (LNA) produced gain of 53.4dB and noise figure (NF) of 1.2dB. The input reflection (S11) and output return loss (S22) are -24.3dB and -23.9dB respectively .The input sensitivity is compliant with the IEEE 802.16 standards.